KETAHANAN BEBERAPA GENOTIPE PADI TERHADAP PENYAKIT HAWAR DAUN BAKTERI (XANTHOMONAS ORYZAE PV. ORYZAE) - Wira Hadianto; Lukman Hakim; Bakhtiar . (Universitas Lampung, 2015)
The resistance rice genotypes against bacterial leaf blight (Xanthomonas oryzae pv. oryzae). The research was conducted to analyze genotypes of rice that were resistant to bacterial leaf blight (BLB) disease. The experiment was conducted at the screen house of Faculty of Agriculture, Syiah Kuala University, Banda Aceh from February to October 2014. This experiment was arranged in randomized complete block design with 73 treatments and 3 replications. IR-BB27 and IR-64 were used as control of resistant and susceptible varieties to BLB, respectively. The result showed that the bacterial isolates tested were virulent. The longest incubation period found in Limboto, Inpari 10, Situ Patenggang, Sirendeh Semantuk Wayla, Tamboen, Sepasie, Bontok and Arias. Genotypes Inpari 1, Limboto, Tuwoti, Inpari 10, Lekat Rambot Linuet, Rom Mokot, Paki Gajah, Tamboen, Bo 100, Sipasie, Bo Minyek, Bontok, Sirendeh Semantuk Wayla and Sambei showed resistance reaction to bacterial leaf blight disease.